2020
DOI: 10.1055/s-0040-1708587
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Facial Artery for Free Functioning Muscle Transfers: An Alternative Pedicle for Salvage in Brachial Plexus Lesions with Vascular Injuries

Abstract: Free functional muscle transfer (FFMT) is a salvage procedure recommended in cases of brachial plexus injury with late presentations or failures of primary nerve reconstruction. The workhorse for most authors is the gracilis, and the most common indication is the restoration of elbow flexion. For successful revascularization of the muscle, donor vessels must be in proximity of the site of the muscle fixation and allow direct coaptation to a donor nerve, ideally without the use of nerve grafts. A major problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A recent article by Bhatia, et al demonstrated the use of the facial artery from the external carotid system for salvage of FFMT where previous SAVI had occurred. 9 In this cohort of patients only two underwent FFMT in the setting of SAVI, which was due to the paradigm shift of treatment away from nerve grafting to FFMT that occurred only at the end of this study period.…”
Section: Discussionmentioning
confidence: 99%
“…A recent article by Bhatia, et al demonstrated the use of the facial artery from the external carotid system for salvage of FFMT where previous SAVI had occurred. 9 In this cohort of patients only two underwent FFMT in the setting of SAVI, which was due to the paradigm shift of treatment away from nerve grafting to FFMT that occurred only at the end of this study period.…”
Section: Discussionmentioning
confidence: 99%